Energy and Load Aware Routing Protocol for Internet of Things - S. Sankar; P. Srinivasan (International Journal of Advances in Applied Sciences, 2018)
Maximizing the network lifetime is one of the major challenges in Low Power and Lossy Networks (LLN). Routing plays a vital role in it by minimizing the energy consumption across the networks through the efficient route selection for data transfer. IPv6 Routing Protocol for Low Power and Lossy Networks (RPL) is a IETF standardized IPv6 routing protocol for LLN. In this paper, we propose Energy and Load aware RPL (EL-RPL) protocol, which is an enhancement of RPL protocol. It uses a composite metric, calculated based on expected transmission count (ETX), Load and battery depletion index (BDI), for the route, selection. The COOJA simulator is used for performance evaluation.  EL-RPL is compared with other similar protocols RER(BDI) RPL and fuzzy logic based RPL (OF-FL RPL). The simulation result shows that the EL-RPL improves the network lifetime by 8-12% and packet delivery ratio 2-4%.